Effects of post-weld heat treatment on microstructure and mechanical properties of linear friction welded Ti2AlNb alloy. (15th March 2016) - Chen, X.; Xie, F.Q.; Ma, T.J.; Li, W.Y.; Wu, X.Q.
Abstract: Linear friction welds of a Ti2 AlNb-based alloy were subjected to post-weld heat treatment (PWHT) at 815 °C × 1 h (PWHT1) and at 1000 °C × 1 h + 815 °C × 2 h (PWHT2) followed by air cooling. The microstructure and mechanical properties of the joints under as weld and PWHT conditions were investigated. The results indicate that in the as weld joint, the weld zone mainly consists of B2 phase while the quantity of α2 and O phase is relatively small, and most O phase gradually turns into B2 phase when the amount of α2 phase reduces as well in thermo-mechanically affected zone (TMAZ). After PWHT1, O precipitates within recrystallized B2 grains can be found in weld zone and the decomposition of α2 phase caused by niobium diffusion is found in TMAZ. PWHT1 have significantly enhanced the mechanical properties due to the O phase precipitation hardening and refined grain strengthening. And the coarsening of the microstructure in weld zone under PWHT2 is evident, which consequently reduces the elongation. Graphical abstract: Highlights: Post-weld treatments significantly affect the microstructure of Ti2 AlNb joint. Acicular O phases have precipitated within B2 grains after post-weld heat treatments. The high temperature and holding time have interaction on grain growth in weld zone. The refined B2 grains and O precipitates enhanced the mechanical properties of the joint.